DAYA SIMPAN DAN KADAR VITAMIN A NUGGET DENGAN SUBTITUSI TEPUNG MULTIGIZI (TUMIZ) - Nadimin Nadimin; Theresia Dewi kartini B; Maulud Fitrah Saputra (Media Gizi Pangan, 2023)
Nuggets are a food product that is widely liked by children and teenagers, but they have an imbalanced nutritional composition and lack vitamin A. Multinutrient flour (Tumiz) is a local functional food product that contains complete nutrients, including vitamins and minerals. The addition of specific ingredients to food can affect the quality of the food product during storage. This study aims to determine the shelf life and vitamin A content of nuggets with the addition of Tumiz.The research was conducted in a laboratory by comparing five types of nuggets made from five Tumiz formulations: 0% Tumiz concentration (X0), 20% Tumiz (X1), 25% Tumiz (X2), 30% Tumiz (X3), and 35% Tumiz (X5). Shelf life was evaluated based on sensory changes in color, aroma, and texture. Moisture content was measured at the beginning and end of storage (pre-post test design) using the Gravimetric method. Vitamin A content was analyzed using the Spectrophotometric method.Tumiz-enriched nuggets started to undergo color changes on the 13th day, while the color of the original nuggets did not change until the 15th day. The aroma of Tumiz-enriched nuggets began to change on the 5th day, whereas the original nuggets only changed on the 10th day. Texture changes in Tumiz-enriched nuggets started on the 5th day, while the original nuggets started to change on the 8th day. The final moisture content of Tumiz-enriched nuggets ranged from 11.8% to 14.16%, which was higher than the moisture content of the original nuggets (11.29%). The vitamin A content of Tumiz-enriched nuggets was approximately 1.61-2.0 µg higher than that of the original nuggets (1.49 µg).Tumiz-enriched nuggets have a shorter shelf life compared to the original nuggets, but they have a higher vitamin A content.